Reconceptualizing learning loss in post-pandemic Indonesia: a literature-based analysis of the pancasila student profile and qur’anic humanistic values - Windy Dian Sari; Armai Arief; Muhammad Hariyadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
The COVID-19 pandemic has intensified learning loss in Indonesian education, not only in terms of academic achievement but also in students’ psychosocial development and character formation. While existing studies have predominantly conceptualized learning loss as a cognitive and instructional problem, limited attention has been given to its ethical, spiritual, and value-based dimensions within post-pandemic educational discourse. This article addresses this conceptual gap by examining how learning loss is discussed in the literature and how character education grounded in national and religious values may be theoretically integrated into this discussion. Employing a conceptual literature review, this study analyzes peer-reviewed journal articles, academic books, policy-related educational literature, and selected Qur’anic exegesis relevant to learning loss, character education, and humanistic learning in the Indonesian context. The analysis is conducted through a thematic and conceptual synthesis, focusing on patterns of thought, normative assumptions, and theoretical linkages across the literature. The findings reveal three interrelated conceptual themes: (1) the reconceptualization of learning loss as a multidimensional phenomenon encompassing academic, psychosocial, and moral dimensions; (2) the role of the Pancasila Student Profile as a normative framework for character education in post-pandemic Indonesia; and (3) the convergence between Qur’anic humanistic values and national character education in shaping holistic educational aims. Based on this synthesis, the article proposes an integrative conceptual framework that situates learning loss within a broader discourse of humanistic and value-based education. Rather than offering empirical solutions, this study contributes theoretically by refining the conceptual understanding of learning loss and highlighting directions for future research on character education and spiritually grounded pedagogical frameworks in post-pandemic contexts.